The strange non-death of neoliberalism - Crouch, Colin 1944- (Polity Press, 2011)
"The financial crisis of 2008-9 seemed to present a fundamental challenge to neo-liberalism, the body of ideas that have constituted the political orthodoxy of most advanced economies in recent decades ... Colin Crouch argues that neoliberalism will shrug off this challenge. The reason is that although it seems to be about free markets, in practice neoliberalism is concerned with the dominance over public life of the giant corporation. This has been intensified, not checked, by the financial crisis and by an acceptance that certain financial corporations are 'too big to fail'. Although much political debate remains preoccupied with conflicts between the market and the state, the impact of the corporation on both [of] these is far more important today"--Back cover.